Polissacarídeos de parede celular fúngica: purificação e caracterização - Fukuda, Eliane Kaori; Vasconcelos, Ana Flora Dalberto [UNESP]; Matias, Andreza Cândido [UNESP]; De Melo Barbosa, Aneli; Dekker, Robert Frans Huibert; Da Silva, Maria de Lourdes Corradi [UNESP] (Universidade Estadual de Londrina, 2009)
The cell wall is a rigid structure essential for the survival of fungi. A knowledge of its composition is therefore useful for the development of novel anti-fungal drugs. In this context, polysaccharides as main components of the fungal cell wall have been the subject of intense scientific study over the years. The information gained from the knowledge of the structure of these macrobiomolecules could therefore be valuable in elucidating the mechanisms of their biosynthesis in the cell walls of pathogenic fungi infecting plants and animals alike. Determination of the chemical structures of these polysaccharides (endo) is preceded by their extraction and purification. The extractions, generally lead to neutral and/ or alkaline soluble biopolymers in groups according to their solubilities. Mixtures of polysaccharides in these extracts can then be purified by a combination of chemical and chromatographic methods. Following purification, the polysaccharides, considered homogeneous, can be characterized structurally using conventional techniques of carbohydrate chemistry, such as hydrolysis, methylation analysis, and FT-IR, 13C- and 1H- NMR spectroscopy. This review surveys the main scientific literature that characterizes polysaccharides constituting the fungal cell wall.
Fungal cell wall polysaccharides: Purification and characterization
Keywords: Biomass; Chemical characterization; Fungal cell wall; Polysaccharides